Fish Parasites, Host Parasite interaction, Economic Burden, Zoonotic Risks, and Sustainable Control Strategies with Special Refence to Pakistan - Inayat Ullah; Bibi, Chand; Baset, Abdul; Fawad, Muhammad; Sunny, Farhat (Indus Journal of Bioscience Research, 2025)
Fish parasites represents, growing threat to global aquaculture, wild fisheries and public health due to their complex life cycles, high pathogenicity, and increasing zoonotic potential. This review highlights the host-parasite interactions, economic impact, and diagnostic challenges of the main groups of fish parasites, such as protozoans, trematodes, cestodes, nematodes, crustacean ectoparasites, and myxozoans. This paper also highlights the role of climate change in altering parasites distribution and accelerating diseases emergence, particularly in aquaculture system under environmental stress. Regional problems, particularly in Pakistan, are highlighted to support the call for enhanced surveillance, diagnostics, and control measures in developing nations. Emergency treatment methods and integrated management practice are reviewed, with a focus on sustainable alternatives to traditional chemotherapeutants. By synthesizing current research and identifying knowledge gaps, this paper aims to assist aquaculture professionals in formulating adaptive measures in parasite management amidst ecological and societal transformations.